Civil Societies and Social Movements - PURDUE, Derrick (Routledge, 2007)
The authors adopt a broad range of research approaches, from testing hypotheses drawn from rationale choice theory against available statistics on associations, to ethnographic study of emerging attempts at participant / deliberative democracy